РЕҢЛИ СҮЎРЕТ ЖӘРДЕМИНДЕ ЖАСЛАРДА КӨРКЕМ-ЭСТЕТИКАЛЫҚ МӘДЕНИЯТЫНЫҢ ҚӘЛИПЛЕСИЎ ҲӘМ РАЎАЖЛАНЫЎ ЖОЛЛАРЫ - Сайтбекова, А.Ж. (SCIENCE and SOCIETY, 2022)
The article is devoted to the modern content of the issue of the formation and development of the artistic and aesthetic culture of youth on the basis of fine arts, and in particular painting. Since in modern society attention has increased to the problem of forming a comprehensively developed, spiritually rich and creative personality. Therefore, the educational process must be based on the creation of conditions for the upbringing of a creative personality, ready for dialogue, cooperation and co-creation in various spheres of life.
Keywords: pedagogy; aesthetic culture; creative development of personality; artistic culture; educational process; fine arts; painting